Mediating effect of family support on the relationship between acculturation and loneliness among the migrant elderly following children in Jinan, China - Zong, Di; Lu, Zhongqian; Shi, Xinfei; Shan, Ying; Li, Shixue; Kong, Fanlei (Frontiers in Public Health, 2022)
The total number of migrant elderly following children (MEFC) has gradually increased along with population aging and urbanization in recent decades in China. The purpose of this study was to investigate the mediating effect of family support on the relationship between acculturation and loneliness among the MEFC in Jinan, China. A total of 656 MEFC were selected by multistage cluster random sampling. Loneliness was measured using the short-form UCLA Loneliness Scale (ULS-8), while acculturation and family support were assessed using a self-designed questionnaire. Descriptive analysis, univariate analysis, and the structural equation model (SEM) were conducted to illustrate the relationship between the above indicators and loneliness. The average ULS-8 score of the MEFC was 12.82 ± 4.05 in this study. Acculturation of the MEFC exerted a negatively direct effect on loneliness and a positively direct effect on family support simultaneously, while family support exerted a negatively direct effect on loneliness. Family support partially mediated the relationship between acculturation and loneliness [95% CI: −0.079 to 0.013, p < 0.001], while the mediating effect of family support accounted for 14.0% of the total effect. The average ULS-8 score of 12.82 ± 4.05 implied a low level of loneliness in the MEFC in Jinan, China. Acculturation was found to be correlated with loneliness, while the mediating role of family support between acculturation and loneliness was established. Policy recommendations were provided to reduce loneliness and improve the acculturation and family support of the MEFC according to the findings above.